What is deductive reasoning in geometry

Answers

Answer 1
Answer: Deductive reasoning is a valid form of proof.
Answer 2
Answer: deductive reasoning is the process by which a person makes conclusions based on previously known facts.

Related Questions

An environmental agency studying the effects of drought on a lake found that the water level decreased at a constant rate during the first few months of the drought. When the agency began its research, the depth of the lake was 346 feet. The table represents the agency’s susequent observations about the lake's depth.Which equation represents the depth of the lake, y, based on the number of weeks passed, x? y = -0.6x + 346 y = -1.2x + 346 y = -0.6x y = -1.2x
Assume that lines a and b are parallel, and the given angles are given in degrees. What is the value of x? (Equation: 2x + 90 = x + 95)
How does the speed change on the Graph? And what does a steeper line mean?
If you formed an algebraic expression to model the phrase "the quotient of three and a number," which operation would you need?a. addition b. subtraction c. multiplication d. division User: Which algebraic expression would not be equivalent if the number and the variable were reversed?a. n + 8b. m – 5c. k x 8d. 4 + x
1. what is the GCF of the terms of 8c^3+12c^2+10c? A.2B.4C.2cD.4c2. How can the polynomial 6d^4+9d^3-12d^2 be factored l?

Solve each system of equations using substitution. Show all work.1) x + y = 1
2x - y = -2

2) 5x - 3y = -11
x - 2y = 2

3) x - y = 3
6x + 4y = 13

Answers

it would be so much easier with elimination but ok
1.
x+y=1
minus x
y=1-x
sub
2x-(x-1)=-2
2x-x+1=-2
x+1=-2
x=-3
sub
y=1-x
y=1-(-3)
y=1+3
y=4
(-3,4)

2.
x-2y=2
add 2y
x=2y+2
sub
5(2y+2)-3y=-11
10y+10-3y=-11
7y+10=-11
7y=-21
y=-3
sub
x=2y+2
x=2(-3)+2
x=-6+2
x=-4
(-3,-4)

3.
x-y=3
add y
x=y+3
sub
6(y+3)+4y=13
6y+18+4y=13
10y+18=13
10y=-5
y=-1/2
sub
x=y+3
x=-1/2+3
x=5/2

(5/2,-1/2)


1. (-3,4)
2. (-3,-4)
3.(5/2,-1/2)

What is the best estimate for the mass of a bicycle

Answers

Answer:

10 kilograms

Step-by-step explanation:

D for dog

Answer:

1o kilo dog

please mark me as brainliest please

Um so how would you treat a big open wound that u can not put a bandaid on?

Answers

Answer:

wrap in gauze

Step-by-step explanation:

How do i find the unknown side length of a triangle?

Answers


By using Pythagoreans Theorem: a^2 + b^2 = c^2
several ways like somebody said below you can use use pythag assuming u know the other 2 side lengths w/ a^2+b^2=c^2
however if you do not know the other two side lengths you must use trigonometry and sohcahtoa
sin(angle)= the side length opposite the angle to be referred to as O
divided by the longest side length (hypotenuse)or the angle directly across from the 90 degree angle to be referred to as H
cos(angle) the side length adjacent (next to) the known angle to be referred to as A/H
and finally tan(angle)O/A
if you are still having trouble with this id suggest youtubing "get triggy with it" decent video that explains trig pretty well  as well as how to find a missing angle rather than a side length
hope this helps -j

Which function in vertex form is equivalent to f(x) = 4 + x2 – 2x?

Answers

The question is asking us to find which function in the vertex form is equivalent to f ( x ) = 4 + x^2 - 2 x. We have to add 1 to make a squared binomial ( and also to subtract 1 ). f ( x ) = ( x^2 - 2 x + 1 ) - 1 + 4 = ( x - 1 )^2 + 3. Then we have the vertex point ( 1, 3 ). Answer: The function in vertex form is: f ( x ) = ( x - 1 ) ^2 + 3.

Answer:

Vertex form of the function will be f(x) = (x - 1)² + 3.

Step-by-step explanation:

Vertex form of a quadratic function is given by f(x) = a(x - h)² + k

where (h, k) is the vertex of the given parabola.

Now we will convert the function in the vertex form.

f(x) = x² - 2x + 1 + 3

     = (x - 1)² + 3

Therefore, the vertex form of the function will be f(x) = (x - 1)² + 3

and the vertex will be (1, 3).

find the lateral area and surface area of a right cone with radius 6 in. and height 8 in. give your answers in terms of pie

Answers

r=6in\n\nH=8in\n\nA=\pi rl\n\nPythagoras\ theorem:\n\nr^2+H^2=l^2\n\nl^2=6^2+8^2\n\nl^2=36+64\n\nl^2=100\n\nl=√(100)\n\nl=10\ (in)

A=\pi\cdot6\cdot10=60\pi\ (in^2)